The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1142/s0218271818430071
|View full text |Cite
|
Sign up to set email alerts
|

The art of the state

Abstract: Quantum field theory (QFT) on curved spacetimes lacks an obvious distinguished vacuum state. We review a recent no-go theorem that establishes the impossibility of finding a preferred state in each globally hyperbolic spacetime, subject to certain natural conditions. The result applies in particular to the free scalar field, but the proof is model-independent and therefore of wider applicability. In addition, we critically examine the recently proposed “SJ states”, that are determined by the spacetime geometry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Subsequently Sorkin (2011a) showed that the construction is also valid in the continuum, and can be used to give an alternative definition of the quantum field theory vacuum. This Sorkin-Johnston (SJ) vacuum provides a new insight into quantum field theory and has stimulated the interest of the algebraic field theory community (Fewster and Verch 2012;Brum and Fredenhagen 2014;Fewster 2018). The SJ vacuum has also been used to calculate Sorkin's spacetime entanglement entropy (SSEE) (Bombelli et al 1986;Sorkin 2014) in a causal set Sorkin and Yazdi 2018).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently Sorkin (2011a) showed that the construction is also valid in the continuum, and can be used to give an alternative definition of the quantum field theory vacuum. This Sorkin-Johnston (SJ) vacuum provides a new insight into quantum field theory and has stimulated the interest of the algebraic field theory community (Fewster and Verch 2012;Brum and Fredenhagen 2014;Fewster 2018). The SJ vacuum has also been used to calculate Sorkin's spacetime entanglement entropy (SSEE) (Bombelli et al 1986;Sorkin 2014) in a causal set Sorkin and Yazdi 2018).…”
Section: Overviewmentioning
confidence: 99%
“…Since the SJ vacuum is intrinsically defined, at least in finite spacetime regions, one has a uniquely defined vacuum. As a result, the SJ state has generated some interest in the broader algebraic field theory community (Fewster and Verch 2012;Brum and Fredenhagen 2014;Fewster 2018). For example, while not in itself Hadamard in general, the SJ vacuum can be used to generate a new class of Hadamard states (Brum and Fredenhagen 2014).…”
Section: The Sorkin-johnston (Sj) Vacuummentioning
confidence: 99%
“…A remarkable fact is that the Hadamard condition (7), together with the algebraic relations in A (M), fixes the two-point function up to smooth terms (see [30,31] for reviews and original references). In particular, the difference of any two Hadamard two-point functions is smooth.…”
Section: Definitionmentioning
confidence: 99%
“…Since it is impossible to choose a distinguished ("vacuum") state which is Hadamard consistently for an arbitrary spacetime [37,38], the first possibility involves an arbitrary choice for each spacetime. In contrast, the second possibility is uniquely defined for an arbitrary spacetime.…”
Section: )mentioning
confidence: 99%